Public Administration in Viewing Problems in the Bureaucracy During the Pandemic - Kurhayadi (Global Writing Academica Researching and Publishing, 2022)
Many things have changed due to the emergence of the Covid-19 pandemic, including how the government manages its bureaucracy. This research will then aim to see how the public administration sees the bureaucracy can continue to run according to its function during the Covid-19 pandemic. This research will use a qualitative approach through a literature study method that will use relevant previous research and studies as data sources. This research then finds two main challenges that the bureaucracy needs to face during the pandemic. This challenge is internal in the form of efforts to regulate the resources owned so that the obligations of the bureaucracy can follow the duties and functions it has. The second challenge is how the community can continue to accept the services provided by the bureaucracy when there are various limitations in delivering public services.